Developing an authoring environment for procedural task tutoring systems : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Computer Science at Massey University, Palmerston North, New Zealand - Smith, Shamus Paul (Massey University, 1997)
The use of computers in education is becoming more and more common as the price of technology drops and its general availability is increased. Unfortunately, building computer based tutoring systems is a difficult process which is fraught with many problems. A significant problem in this area is the lack of reuse of system components between computer tutor developments. This means that each new system must be started from scratch and mistakes from earlier projects can easily be repeated. A complementary difficulty is the variety of specialist skills that are required to build these systems. Typical developers do not usually possess the combination of domain, cognitive science and programming knowledge that is needed to build computer tutors. One solution to these problems is the use of an authoring environment for facilitating the building of computer based tutoring systems. This thesis presents an authoring tool for the construction of computer based tutoring systems teaching procedural tasks in a discovery learning environment. TANDEM (Task ANd Domain Environment Model) provides tools for domain and task definition, sub-domain definition and a domain independent tutoring engine. It is argued that such an environment can provide a non-expert user with access to advanced techniques from artificial intelligence research for knowledge acquisition and representation. Several tasks from the construction process have been automated, thus simplifying this activity. The use of sub-domain partitioning has been considered and techniques for the integration of custom built domain interfaces are described. Also, it is proposed that by providing a domain independent tutoring engine, reuse can be encouraged over numerous domains which can reduce the development time required to build these systems.
Keywords: Computer-assisted instruction; Authoring programmes; Computer software